VHE γ-ray discovery and multiwavelength study of the blazar 1ES 2322−409 - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Schwemmer, Stephanie; Wagner, Stefan; Rieger, Frank M. (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. A hotspot at a position compatible with the BL Lac object 1ES 2322−409 was serendipitously detected with H.E.S.S. during observations performed in 20